Studies on growth of Au cube-ZnO core-shell nanoparticles for photocatalytic degradation of methylene blue and methyl orange dyes in aqueous media and in presence of different scavengers. Issue 4 (August 2019) - Verma, Shweta; Tirumala Rao, B.; Jayabalan, J.; Rai, S.K.; Phase, D.M.; Srivastava, A.K.; Kaul, R.
Graphical abstract: Highlights: Annealing improves crystalline quality and dye degradation efficiency. Optimum nanoparticles loading and role of dye concentration on its degradation. Different scavengers at high concentration inhibit the dye degradation process. Hydroxyl radical contribution dominates in degradation of cationic and anionic dyes. High pH conditions are favorable for faster degradation of the dyes. Abstract: Au-ZnO core-shell nanoparticles with cubic Au core were synthesized using ascorbic acid assisted hydrothermal growth method. Variation in optical response, surface plasmon resonance of Au nanocubes during shell layer growth was studied and explained with numerical calculations. Annealing induced changes in optical absorption, crystalline quality and morphology of these nanoparticles was addressed. Annealing at high temperatures (≥ 400 °C) was found to be important for significant improvement of photocatalytic activity of these nanoparticles. Photocatalytic response of the nanoparticles was studied through degradation of methylene blue (MB) and methyl orange (MO) dyes. Role of different process parameters mainly dye concentration, type of UV lamp, nanoparticle loading, presence of different scavengers at varied concentrations and solution pH on dye degradation was addressed. The results reveal that hydroxyl radical plays vital role in the degradation process. The effect of scavengers and their concentration is almost similar for both these dyes degradation. High pH was found to enhance the degradation process and its rate constant increased by 15 and 8 times at pH 12 for MB and MO respectively. These nanoparticles of 1 g/L loading were efficient to degrade the dyes with concentration of about 15 mg/L, within an hour (three hrs.) in high pH (neutral) solutions. The growth process was optimized for easy collection of the nanoparticles for large quantity handling. The core-shell nanoparticles used in the study are environmental friendly and their synthesis along with dye degradation in low power light is cost effective for treatment of industrial wastewater containing different dyes.